Pengaruh Likuiditas, Leverage, dan Sales Growth Terhadap Profitabilitas pada Perusahaan Sektor Healthcare Yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2019-2023 - Aisyah Aisyah; Andri Indrawan; Evi Martaseli (AKUNTANSI 45, 2024)
his study aims to analyze the influence of liquidity (CR), leverage (DER), and sales growth on profitability (ROA) in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. This research employs a quantitative approach. The population consists of healthcare sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample comprises 21 healthcare sector companies listed on the IDX during the same period, selected using purposive sampling technique. The research model utilizes classical assumption tests (Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test), multiple linear regression, hypothesis testing (t-Test and F-Test), and coefficient of determination test. The final results indicate that simultaneously, CR, DER, and Sales Growth affect ROA. Partially, CR and Sales Growth do not have a significant influence on ROA, while DER has a negative and significant effect on ROA.